Traveling-Wave-Based Fault Location in Electrical Distribution Systems With Digital Simulations - Jinrui Tang; Xianggen Yin; Zhe Zhang (Universitas Ahmad Dahlan, 2014)
Traveling-wave-based fault location in electrical distribution systems is an important safeguard for the distribution network reliability. The effectiveness of the methods is verified directly in power grid in the early stages, while different fault types can't appear in a short time. And normal dynamic physical simulation cannot meet the teaching demand either because of the limitation of transmission line model and other factors. So PSCAD/EMTDC and MATLAB are used to illustrate the the fault location methods in this paper, which can promote the traveling-wave-based fault-location technology. Meanwhile, the traveling-wave-based fault-location method based on characteristic frequencies is analyzed in this paper.